Development of radiation shielding material based on natural rubber/ boron oxide and metal oxide composites - Buasuwan, Nichapa; Pinprayoon, Orawan; Changnoi, Siriporn; Rungseesumran, Thiti (Bulletin of Applied Sciences, 2023)
Radiation protective rubber sheet for producing neutron radiation, X-rays and gamma rays protection suits are developed from natural rubber mixed with boron oxide for neutron radiation protection, lead oxide and tungsten oxide for protection against X-rays and gamma rays. The study of neutron radiation shielding properties from 241Am-Be (Americium-Beryllium) neutron source found that, at the same thickness of 2 mm, rubber compound containing boron oxide 40 phr provided a neutron radiation attenuation value of 18 percent, gave better attenuation comparing to those with vary amounts of boron oxide. The neutron attenuation values are similar to shielding materials polyethylene which commercially available that gives a neutron radiation attenuation value of 11 percent. But the boron oxide filled rubber sheet, when formed, the rubber sheet formed small white flakes all over the sheet and the physical properties of the tensile strength were very low. Therefore, this formulation of rubber sheets is not suitable for the production of radiation protection suits. This research also studied the X-ray shielding properties by using X-ray source and gamma-ray generated from 137Cs gamma-ray source. The efficiency of X-ray shielding increases with the amount of lead oxide and tungsten oxide. It was found that, at the same thickness of 2 mm, the formula with 500 phr lead oxide had an X-ray attenuation value of 87 percent and gamma ray attenuation value of 8.8 percent and the formula with 900 phr tungsten oxide had an X-ray attenuation value of 85 percent. Gamma rays 8.3 percent, which had better attenuation values than commercially available radiation protection suits had an X-ray attenuation value of 84 percent and a gamma ray attenuation value of 6.2 percent. Physical properties of radiation protection rubber sheet, namely hardness, tensile strength, elongation at break and tear strength are also studied. It was found that the radiation protection rubber sheet (500 phr) an increase in radiation protection substance resulted in a decrease in their physical properties to an acceptable level. However, the radiation protection rubber sheet with tungsten based (900 phr) has very low tensile properties, therefore proper application has to be more considered.